Indicators of Post-Operative Intraocular Pressure Elevation after Naïve Fluocinolone Acetonide Surgical Implantation. (3rd July 2020) - Sadowsky, Aaron J.; Pecen, Paula E.; Feinstein, Eric; Palestine, Alan G.
ABSTRACT: Purpose: To determine factors conferring an increased risk of developing ocular hypertension secondary to the fluocinolone acetonide (FA) sustained-release surgical implant (Retisert). Design: Retrospective, observational case series. Methods: Patients with a history of chronic noninfectious posterior uveitis undergoing naïve surgical FA implantation from 2007 to 2018 at the University of Colorado were studied. Patient demographics and multiple clinical measures were noted one year before and after FA implantation. Results: Twenty-nine eyes of 21 patients were studied. The median age experiencing an IOP rise vs median age experiencing no IOP rise post-FA implantation was 27.0 and 54.0 years old, respectively ( p = .01). A pre-FA implant risk factor of needing future glaucoma surgery after FA implantation is prior to maximum IOP ( p = .02). Conclusions: A risk factor of elevated post-FA implantation IOP includes younger age. A potential risk factor for glaucoma surgery after FA implantation was higher maximum IOP before FA implantation.